Mechanisms of Pathogenesis in Listeria monocytogenes Infection I. Influence of Iron - Sword, C. P. (1966)
Sword, C. P. (The University of Kansas, Lawrence). Mechanisms of pathogenesis in Listeria monocytogenes infection. I. Influence of iron. J. Bacteriol. 92: 536–542. 1966.—The effects of ferric and ferrous iron as well as other cations on Listeria infection in mice were studied. Iron compounds caused a reduction in the ld(50) dose of Listeria, and, when added to a synthetic medium, proved stimulatory for in vitro growth of the organism. Bacterial counts on spleen and liver tissue from iron-treated mice showed that iron injections caused more rapid growth of bacteria and resulted in higher numbers of organisms in the tissue. The reticuloendothelial system did not appear to be impaired by this treatment. Immunized animals were not affected by iron treatment during challenge. Mice with experimentally induced hemolytic anemia showed increased susceptibility to listeriosis, whereas those treated with Desferal, a specific iron-chelating agent, appeared more resistant. Iron proved stimulatory for the avirulent strain, 9037–7, and resulted in an ld(50) of 1.3 × 10(4) organisms in iron-treated animals. Growth of L. monocytogenes and mortality from experimental infection appeared to be correlated with availability of iron to the bacteria. The results suggest that host iron metabolism may play a part in the onset and progress of Listeria infections.